2013
DOI: 10.1074/jbc.m113.464644
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation by the Wilms Tumor Protein, Wt1, Suggests a Role of the Metalloproteinase Adamts16 in Murine Genitourinary Development

Abstract: Background: ADAMTS16 is a mammalian metalloproteinase with unknown function. Results: Transcription of the Adamts16 gene is regulated by Wilms tumor protein Wt1, and knockdown of Adamts16 reduces branching morphogenesis in cultured embryonic kidneys. Conclusion: Adamts16 is a Wt1 target gene during murine genitourinary development. Significance: The findings provide novel insights into gene regulatory networks controlling kidney and gonad development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 64 publications
0
21
1
Order By: Relevance
“…Heterozygous mutant males had a normal migration of their gonads suggesting a recessive feature. Given that Adamts16 is a downstream target of WT1, this study rises suspicion on the role of Adamts16 polymorphisms in cryptorchid men with an otherwise normal function of the WT1 protein …”
Section: Molecular Genetics Of Cryptorchidismmentioning
confidence: 83%
See 1 more Smart Citation
“…Heterozygous mutant males had a normal migration of their gonads suggesting a recessive feature. Given that Adamts16 is a downstream target of WT1, this study rises suspicion on the role of Adamts16 polymorphisms in cryptorchid men with an otherwise normal function of the WT1 protein …”
Section: Molecular Genetics Of Cryptorchidismmentioning
confidence: 83%
“…Given that Adamts16 is a downstream target of WT1, this study rises suspicion on the role of Adamts16 polymorphisms in cryptorchid men with an otherwise normal function of the WT1 protein. 130 Gene specific deletion of Desrt, a novel murine ARID class DNAbinding protein, causes cryptorchidism. 131 No clinical investigation has been reported so far on any gene variation in patients with cryptorchidism.…”
Section: Other Genetic Causes: Lessons From Animal Modelsmentioning
confidence: 99%
“…Although there were 11 known genes ( LOC340094, ADAMTS16, KIAA0947, FLJ33360, MED10, UBE2QL1, LOC255167, NSUN2, SRD5A1, PAPD7, and MIR4278 ) located in the first deletion in 5p15.33p15.31, only a few of them are fully characterized for gene functions and disease association. Recent whole exome sequencing study revealed that homozygous splicing mutation in NSUN2 to be a cause of Dubowitz-like syndrome, an autosomal recessive disorder characterized by the constellation of mild microcephaly, growth and mental retardation, eczema and peculiar facies [31]; The ADAMTS16 gene has been reported to play a role of the metalloproteinase in murine genitourinary development [32], and loss-of-function mutations of the MED10 gene have been previously linked with WNT/GSK3β/β-Catenin pathway function [33]. Only SRD5A1 haploinsufficiency has been speculated to be associated with cerebellar hypoplasia, hypospadias, and facial dysmorphisms in a prenatal study [28].…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS-16 is a member of the ADAMTS family. Expression of Adamts16 has been reported in rodent fetal lung and kidneys, adult brain and ovaries [3], [4], and most recently in mice embryonic and adult rat gonads [5]. Several studies have implicated ADAMTS16 in various pathological conditions, including osteoarthritis [6], [7], colorectal and esophageal cancers [8], hypertension [9], [10] and physical functional impairment in the context of major mental illnesses including bipolar disorder, major depressive disorder and schizophrenia [11].…”
Section: Introductionmentioning
confidence: 99%